2015
DOI: 10.1186/s12885-015-1861-1
|View full text |Cite
|
Sign up to set email alerts
|

Methylation status of TSHr in well-differentiated thyroid cancer by using cytologic material

Abstract: BackgroundThe role of methylation status of the thyroid stimulating hormone receptor gene (TSHr) in the discrimination of benign and malignant thyroid nodules has already been studied using paraffin blocks and cell lines. As cytological sampling plays an important role in assessment of thyroidal nodules, we have investigated the potential clinical use of TSHr methylation status of fine needle aspiration specimens reported according to Bethesda System.MethodSixty nine patients who had both cytological and patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…Studies have also shown a strong association with B-RAF mutations in PTC. This relationship supports the theory that TSHR silencing is a secondary genetic event in thyroid carcinogenesis and not essential for the initiation of thyroid carcinoma ( 32 , 33 ).…”
Section: Molecular Markers Of Thyroseq Next-generation Sequencing Pansupporting
confidence: 85%
See 1 more Smart Citation
“…Studies have also shown a strong association with B-RAF mutations in PTC. This relationship supports the theory that TSHR silencing is a secondary genetic event in thyroid carcinogenesis and not essential for the initiation of thyroid carcinoma ( 32 , 33 ).…”
Section: Molecular Markers Of Thyroseq Next-generation Sequencing Pansupporting
confidence: 85%
“…Mouse models have shown that TSHR is required for thyroid carcinogenesis. It is still uncertain whether this supports TSHR’s role in the initiation of thyroid carcinoma or it is simply due to the TSHR-dependent generation of thyroid cells from which carcinogenesis initiates ( 20 , 32 , 33 ).…”
Section: Molecular Markers Of Thyroseq Next-generation Sequencing Panmentioning
confidence: 99%
“…Thyroid cancer is classified into three types: Well-differentiated; poorly-differentiated; and undifferentiated ( 3 ). The most prevalent types of thyroid cancer are well-differentiated [papillary thyroid cancer (PTC) and follicular thyroid cancer (FTC)] thyroid carcinomas, which make up ~93% of all thyroid cancers ( 4 , 5 ). In addition, the incidence of well-differentiated thyroid cancers (WDTC) has increased dramatically in the past decade ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation of TSHR plays a crucial role in thyroid carcinogenesis [ 97 99 ]. Hyper methylation of the TSHR promoter is frequently found in thyroid carcinoma, although the promoter is un-methylated in normal and benign thyroid tumors [ 28 , 85 , 98 – 100 ]. The pooled OR in our study indicated that TSHR had an important role in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%